IMPLEMENTASI NILAI KARAKTER DI SEKOLAH STUDI OBSERVASI PADA SISWA SMPSK BATARENDE WOLOSAMBI - Falentinus Mite; Marianus Ghepa Mite; Silvester Loy; Mufazal Ramadan Syaiful; Robertus Lili Bile (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This observation, entitled "Implementation of Character Values in Schools: An Observational Study of Students at Batarende Wolosambi Junior High School." The purpose of this observation was to analyze how character values such as discipline, responsibility, cooperation, and honesty are implemented in the school environment. This observation used a qualitative observation design. Data collection methods used were observation, interviews, and documentation. The results of the observation indicate that Batarende Wolosambi Junior High School implements character values in schools, including: 1) Integration into learning; 2) Daily habits at school; 3) Extracurricular activities as a vehicle for character development; 4) School programs for character strengthening. This observation contributes to the development of character value implementation in the observational study of Batarende Junior High School students. This can be seen based on the observation results and supported by documentation obtained during the observation